Solid waste management in Romania - Schiopu, Ana-Maria; Gavrilescu, Maria; Omran, Abdelnaser (2008)
Pollution and health risks generated by improper solid waste management are important issues concerning environmental management in developing countries including Romania. In most cities, the use of open dumps in common for the disposal of wastes, resulting in soil and water resource contamination by leachate in addition to odors and fires. Solid waste management infrastructure and services in developing countries are far from achieving basic standards in term of hygiene and efficient collection and disposal. The paper presents an overview of current solid waste management (SWM) practices in Romania and suggests solutions to some of the major problems. Urban and rural waste management is considered and collection, transport, processing, recycling or disposal of waste materials is discussed relative to the National Waste Management Strategy and the National Plan for Waste Management, as well as European and national legislative framework. It was showed that land disposal will continue to be a disposal option but due to stricter regulation. Local and regional authorities are heavily and increasingly involved in the management of waste. In most cases, they are responsible for developing and implementing municipal waste management plans based on the medium to long term. Due to an increase in population and changes in lifestyle, the quantity and quality of MSW in Romania has changed. Lack of infrastructural, suitable planning and public awareness are the main challenges of MSW management in Romania.